Development of efficient Agrobacterium-mediated transformation of a second-generation biofuel crop, Brassica carinata - Reshma Roy; Shilpika Kassety; Nelson Gororo; Rick Bennett; Anthony A. Millar; Srinivas Belide (Plant Molecular Biology, 2026)

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

Topically delivered 22 nt siRNAs enhance RNAi silencing of endogenous genes in two species - Bill Hendrix; Wei Zheng; Matthew J. Bauer; Ericka R. Havecker; Jennifer T. Mai; Paul H. Hoffer; Rick A. Sanders; Brian D. Eads; Amy Caruano-Yzermans; Danielle N. Taylor; Chelly Hresko; Janette Oakes; et al. (Planta, 2021)
Main conclusion 22 nt siRNAs applied to leaves induce production of transitive sRNAs for targeted genes and can enhance local silencing. Systemic silencing was only observed for a GFP transgene. Abstract RNA interference (RNAi) is a gene silencing mechanism important in regulating gene expression during plant development, response to the environment and defense. Better understanding of the molecular mechanisms of this pathway may lead to future strategies to improve crop traits of value. An abrasion method to deliver siRNAs into leaf cells of intact plants was used to investigate the activities of 21 and 22 nt siRNAs in silencing genes in Nicotiana benthamiana and Amaranthus cruentus . We confirmed that both 21 and 22 nt siRNAs were able to silence a green fluorescent protein ( GFP ) transgene in treated leaves of N. benthamiana , but systemic silencing of GFP occurred only when the guide strand contained 22 nt. Silencing in the treated leaves of N. benthamiana was demonstrated for three endogenous genes: magnesium cheletase subunit I ( CHL-I ), magnesium cheletase subunit H ( CHL-H ), and GENOMES UNCOUPLED4 (GUN4) . However, systemic silencing of these endogenous genes was not observed. Very high levels of transitive siRNAs were produced for GFP in response to treatment with 22 nt siRNAs but only low levels were produced in response to a 21 nt siRNA. The endogenous genes tested also produced transitive siRNAs in response to 22 nt siRNAs. 22 nt siRNAs produced greater local silencing phenotypes than 21 nt siRNAs for three of the genes. These special properties of 22 nt siRNAs were also observed for the CHL-H gene in A. cruentus . These experiments suggest a functional role for transitive siRNAs in amplifying the RNAi response.

Complimentary address from the President of the American Phytopathological Society - Rick Bennett (Journal of General Plant Pathology, 2015)

Global challenges in plant pathology - Rick Bennett (Journal of General Plant Pathology, 2015)

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

A Model to Evaluate the Cytotoxicity of the Fungal Volatile Organic Compound 1-octen-3-ol in Human Embryonic Stem Cells - Arati A. Inamdar; Jennifer C. Moore; Rick I. Cohen; Joan Wennstrom Bennett (Mycopathologia, 2012)

Exploitation of the late flowering species Brassica oleracea L. for the improvement of earliness in B. napus L.: an untraditional approach - M. Habibur Rahman; Rick A. Bennett; Rong-Cai Yang; Berisso Kebede; Mohan R. Thiagarajah (Euphytica, 2011)

Interspecific cross of Brassica oleracea var. alboglabra and B. napus: effects of growth condition and silique age on the efficiency of hybrid production, and inheritance of erucic acid in the self-pollinated backcross generation - Rick A. Bennett; Mohan R. Thiagarajah; Jane R. King; M. Habibur Rahman (Euphytica, 2008)

An Approach to Predict Risks to Wildlife Populations from Mercury and Other Stressors - Diane Nacci; Marguerite Pelletier; Jim Lake; Rick Bennett; John Nichols; Romona Haebler; Jason Grear; Anne Kuhn; Jane Copeland; Matthew Nicholson; Steven Walters; Wayne R. Munns (Ecotoxicology, 2005)